Mosuli Biographies in (al-durar al-kamina Fi ayan al-Ma,a al-thamina)by Ibn Hijjar Al-asgalani (852 A.H-1449 A.D):A study of their civilizational contributions. : A study of their civilizational contributions - ا. م. د. هدى ياسين يوسف الدباغ ا. م. د. (lark, 2020)
This paper sheds light on some Mosuli personalities that were written in (al-durar aL-kamina by Ibn Hajjar AL-Asgalani They travelled to Bilad al-sham and Egypt,the reasons which prompted made those personalities to leave Mosul and travel to those countries .The civilizational contribution of the Mosuli personalities has been in variety of fields ,among which their contribution to religious sciences especially in Hadith and the ways of reading of the Quran,Those personalities were also outstanding in the administrative and scientific fields.Some became poets,Literary–men and physicians and some wrote works and held administrative positions and important official positions in the Mamluk state Some of those personalities were distinguished in the domain of economy mainly,in particular trade